An efficient algorithm for generation of conforming mesh for three-dimensional discrete fracture networks. Issue 8 (5th November 2018) - Mohajerani, Soheil; Huang, Duruo; Wang, Gang; Jalali, Seyed-Mohammad Esmaeil; Torabi, Seyed Rahman
Abstract : Purpose: This study aims to develop an efficient algorithm for generation of conforming mesh for seepage analysis through 3D discrete fracture networks (DFN). Design/methodology/approach: The algorithm is developed based on a refined conforming Delaunay triangulation scheme, which is then validated using analytical solutions. The algorithm is well able to meet the challenge of meshing complex geometry of DFNs. Findings: A series of sensitivity analysis have been performed to evaluate the effect of meshing parameters on steady state solution of Darcy flow using a finite element scheme. The results show that an optimized minimum internal angle of meshing elements should be predetermined to guarantee termination of the algorithm. Originality/value: The developed algorithm is computationally efficient, fast and is of low cost. Furthermore, it never changes the geometrical structure and connectivity pattern of the DFN.